2011
DOI: 10.1158/1535-7163.mct-11-0381
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the Intracellular MUC1 C-terminal Domain Inhibits Proliferation and Estrogen Receptor Transcriptional Activity in Lung Adenocarcinoma Cells

Abstract: Mucin 1 (MUC1) is a diagnostic factor and therapy target in lung adenocarcinoma. MUC1 C-terminal intracellular domain (CD) interacts with estrogen receptor α (ERα) and increases gene transcription in breast cancer cells. Because lung adenocarcinoma cells express functional ERα and estrogen receptor β (ERβ) we examined MUC1 expression and MUC1-ER interaction. Since blocking MUC1 CD with an inhibitory peptide (PMIP) inhibited breast tumor growth, we tested whether PMIP would inhibit lung adenocarcinoma cell prol… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 42 publications
3
18
0
Order By: Relevance
“…Zuschriften MCF7-secreted exosomes expressed the highest levels of MUC1, HER2, and EpCAM, while the highest expression level of CD63 was found in HeLa-secreted exosomes.T hese findings were consistent with previous reports showing ad rastically upregulated transcription level of cellular MUC1 in MCF-7 [16] and exosomal CD63 in HeLa. [10b] These data also verify the capability of ASPNC to differentiate the subtle variation of protein levels in exosomes from different source cells.…”
Section: Angewandte Chemiesupporting
confidence: 93%
“…Zuschriften MCF7-secreted exosomes expressed the highest levels of MUC1, HER2, and EpCAM, while the highest expression level of CD63 was found in HeLa-secreted exosomes.T hese findings were consistent with previous reports showing ad rastically upregulated transcription level of cellular MUC1 in MCF-7 [16] and exosomal CD63 in HeLa. [10b] These data also verify the capability of ASPNC to differentiate the subtle variation of protein levels in exosomes from different source cells.…”
Section: Angewandte Chemiesupporting
confidence: 93%
“…113 Follow-up studies with PMIP further demonstrated the utility of PMIP as a therapeutic intervention for lung cancer, although neither of these studies focused on metastatic disease. 114,115 In the Kufe laboratory, the ability of MUC1-CD to form dimers was targeted with a peptide-based therapy termed GO-203. 116 GO-203 is a decoy peptide conjugated to the cell penetrating peptide and targeted to the juxtamembrane region of MUC1, which serves as both the non-canonical nuclear conjugated to a MUC1-GST fusion protein (M-FP), or seven injections of placebo after mastectomy.…”
Section: Muc1 Targeted Therapiesmentioning
confidence: 99%
“…MUC1 for example is a prognostic indicator in gastric and colorectal cancer and a marker of progression and metastasis [6]. Inhibition of MUC1 affects its oligomerization domain and signaling in prostate cancer, lung adenocarcinoma, and breast cancer [15][16][17]. Interaction of MUC1/c-Met has been associated with high motility and invasion in pancreatic adenocarcinoma [18].…”
Section: Introductionmentioning
confidence: 99%